The Meaning of Fear of Adultery in Marriage Dispensation Applications at The Sidoarjo Religious Court - Aqila Dwike; Ainul Mardhiah Zabidi (PT Pro Panoramic Solution, 2026)
This study aims to analyze the meaning of the concept of